Malignant Infantile Osteopetrosis with Bone Marrow Involvement (Kathmandu University Medical Journal, 2022)
Osteopetrosis (Marble bone disease) is a very rare congenital genetic disease of skeleton, resulting from defective bone resorption, due to functionally defective osteoclast, leading to accumulation of excessive bone mass. Malignant infantile osteopetrosis (MIO) is one of the varieties of osteopetrosis, which is fatal and is diagnosed in early infancy. Malignant infantile osteopetrosis is present with abnormal bone remodeling, hematological abnormities, features of extramedullary hematopoiesis. Radiology is the key of diagnosis. In this case, we present a 5-month-old male infant diagnosed as malignant infantile osteopetrosis, who presented with bronchopneumonia, anemia, thrombocytopenia, hepatosplenomegaly, failure to thrive (FTT).